How bureaucrats shape political decisions: The role of policy information. (29th December 2020) - Blom‐Hansen, Jens; Baekgaard, Martin; Serritzlew, Søren
Abstract: Studies of bureaucracy have been very concerned about whether the bureaucracy exploits its informational advantage vis‐à‐vis politicians to influence policy decisions. Yet, little theorizing has been undertaken about how such influence takes place. We identify and test three mechanisms that must be at work in order for policy information to function as a vehicle for political influence of bureaucrats. Using data from politicians and bureaucrats in five different political systems and survey experimental methods to deal with endogeneity and social desirability bias, we find evidence supporting all three mechanisms: bureaucrats are generally willing to use policy information to influence political decisions, politicians rely on policy information from bureaucrats when making such decisions, and the way policy information is presented matters for the policy preferences of politicians. We discuss the implications of the results and factors that are important for the mechanisms to apply.